Low frequency stability of hydro-generator-connected power system - Seat, Rayduin Qin Fa. (2012)
In the search for clean energy sources in the world, hydroelectricity is the most widely used form of renewable energy. It accounts for 16 percent of global electricity consumption in 2010. Indeed, a spike in the use of hydroelectricity was observed between 2003 and 2009.Earlier research into this area had investigated the effects of hydro-turbines and load on power system. By comparing the results of various designs and parameter settings of the speed governor control system, the study had demonstrated that the hydro-turbine, speed governor and the frequency-sensitive load do impact on the system low frequency stability margin. The speed governor control system needs to be calibrated properly to avoid instability.